A dose‐escalation study of combretastatin A4‐phosphate in healthy dogs. (16th June 2017) - Abma, E.; Smets, P.; Daminet, S.; Cornelis, I.; De Clercq, K.; Ni, Y.; Vlerick, L.; de Rooster, H.
Abstract : Combretastatin A4‐Phosphate (CA4P) is a vascular disrupting agent revealing promising results in cancer treatments for humans. The aim of this study was to investigate the safety and adverse events of CA4P in healthy dogs as a prerequisite to application of CA4P in dogs with cancer. Ten healthy dogs were included. The effects of escalating doses of CA4P on physical, haematological and biochemical parameters, systolic arterial blood pressure, electrocardiogram, echocardiographic variables and general wellbeing were characterised. Three different doses were tested: 50, 75 and 100 mg m −2 . At all 3 CA4P doses, nausea, abdominal discomfort as well as diarrhoea were observed for several hours following administration. Likewise, a low‐grade neutropenia was observed in all dogs. Doses of 75 and 100 mg m −2 additionally induced vomiting and elevation of serum cardiac troponine I levels. At 100 mg m −2, low‐grade hypertension and high‐grade neurotoxicity were also observed. In healthy dogs, doses up to 75 mg m −2 seem to be well tolerated. The severity of the neurotoxicity observed at 100 mg m −2, although transient, does not invite to use this dose in canine oncology patients.